The antimicrobial effect of piper betel leaves extract against Streptococcus mutans - Mohammad Subri, Liyana; Dewi, Warta; Satari, Mieke Hemiawati (Universitas Padjadjaran, 2012)
Introduction: Betel leaves are herbal plant that is believed to have phenolic compound as an antimicrobial agent. One of the medical plants (herbal) which has an-timicrobial properties is Piper betel.The aim of this research is to analyzed the antimicrobial effect of Piper Betel Leaves extract against Streptococcus mutans. Methods: Type of this research is laboratory experiment. Population of this study are Piper betle Linn plant in West Java. The MIC test were conducted based on serial dilution method in 64%, 32%, 16%, 8%, 4%, 2%, 1%, 0.5%, 0.25%, 0.125% concentration of Piper betel leaves extracts against 5 sample of Streptococcus mutans within three repetitions. Results: The result shows that 0.25% concentration of Piper betel leaves extract can inhibit Streptococcus mutans. Conclusion: Piper betel leaves extract can inhibit the growth and had antimicrobial effect against Streptococcus mutans.